Correlation between Workers’ Characteristics and Health Complaints Due to Exposure to Organic Solvents in the Sidoarjo Offset Printing - Bening Kusuma Ramadhini; Lilis Sulistyorini (Universitas Airlangga, 2021)
Introduction: Organic solvents are chemicals that are often used by the printing industry and contain Benzene, Toluene, and Xylene which are toxic to humans. Chemicals that contain organic solvents are ink, glue, and others. Workers who are regularly exposed to organic solvents can have health complaints. The purpose of this study was to determine the correlation between workers’ characteristics and health complaints due to exposure to organic solvents in the Sidoarjo offset printing. Methods: This research was an observational study with cross sectional design. Population in this research was 30 workers. The sampling technique used simple random sampling and from the calculation results were obtained 24 respondents. This study had an independent variable, which was workers’ characteristics consisting of age, smoking habits, and work tenure. The dependent variable was health complaints of printing workers. Data collection used questionnaires and interviews. The research data were analyzed using fisher’s exact test to show the correlation between workers’ characteristics and health complaints. Results: The result of the analysis test found that there was no correlation between age (p=0.386) and smoking habits (p=0.376) with health complaints of workers. Moreover, the analysis test showed that work tenure variable had a correlation with health complaints of workers (p=0.041). Conclusion: A factor related to health complaints of workers was work tenure.Keywords: health complaints, organic solvents, worker characteristics